The appreciation of the jurisdiction of crimes committed during commercial space flights (Law and Safety, 2023)
The author examines the jurisdictional dilemma of determining the appropriate approach to be applied to a crime that could potentially be committed during a space flight with tourists on board by assessing the place of commission of the crime. In addition, the study is based on comparisons under such sources of international law as the Outer Space Treaty (OST) and the Antarctic Treaty (AT). Based on the analysis of certain articles of these documents, the authors propose to regulate commercial space flights by the example of distinguishing the “tourist element”. This approach is based on the fact that Article 8 of the Antarctic Treaty specifically refers to the tourist as a subject of liability and that a person with tourist purposes is protected by national law. Therefore, for the proper international regulation of space tourism and improvement of the Outer Space Treaty, it is recommended to legitimise tourist purposes and to distinguish the status of non-astronaut tourists in order to establish liability for certain criminal acts.To support these initiatives, two cases are cited as examples: that of astronaut Ann McClain and Dr. Rodney David Marks. Thus, the first case emphasises the restricted applicability of criminal jurisdiction on the international space station, which is usually decided by the law of the country of a person’s nationality. The second case demonstrates that although the Antarctic Treaty can serve as an example for regulating space tourism, the jurisdictional battles between states on the territory of the site of an incident with a criminal element have undermined its effectiveness. Consequently, the authors conclude that it is necessary to introduce specific international rules to regulate commercial space flights, where the aspect of jurisdiction in the investigation of a crime committed by a non-astronaut tourist should be of paramount importance.It is specified that each partner of a space flight, both the state (in the case of public interests) and/or certain flight authorities operating under the auspices of a particular country, and a space company and/or a provider of relevant services (in the case of private interests), must register a commercial space flight and its structural objects as flight elements.In this case, each of these partners retains jurisdiction and control over the registered components.
Keywords: space tourism; non-astronaut tourist; outer space jurisdiction; astronaut Ann McClain; scientist Rodney David Marks; Outer Space Treaty; Antarctic Treaty.